2015
DOI: 10.1111/bph.13319
|View full text |Cite
|
Sign up to set email alerts
|

High‐density lipoprotein inhibits human M1 macrophage polarization through redistribution of caveolin‐1

Abstract: BACKGROUND AND PURPOSEMonocyte-derived macrophages are critical in the development of atherosclerosis and can adopt a wide range of functional phenotypes depending on their surrounding milieu. High-density lipoproteins (HDLs) have many cardio-protective properties including potent anti-inflammatory effects. We investigated the effects of HDL on human macrophage phenotype and the mechanisms by which these occur. EXPERIMENTAL APPROACHHuman blood monocytes were differentiated into macrophages in the presence or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 50 publications
4
45
0
1
Order By: Relevance
“…And our data also were in line with published reports that most actions of ANG II were primarily carried out by AT 1 R signaling . Additionally, inhibition of Erk1/2, p38, or Stat3 could also obviously ameliorate the cardiac injury, which cannot completely owe to prevent M1 polarization; as all these inhibitors are not specific for macrophage polarization, more and more data indicated that macrophage polarization was associated with Erk1/2, p38, or Stat3; therefore, our data suggested that to prevent the macrophage polarization, the EAM development could be ameliorated.…”
Section: Discussionsupporting
confidence: 91%
“…And our data also were in line with published reports that most actions of ANG II were primarily carried out by AT 1 R signaling . Additionally, inhibition of Erk1/2, p38, or Stat3 could also obviously ameliorate the cardiac injury, which cannot completely owe to prevent M1 polarization; as all these inhibitors are not specific for macrophage polarization, more and more data indicated that macrophage polarization was associated with Erk1/2, p38, or Stat3; therefore, our data suggested that to prevent the macrophage polarization, the EAM development could be ameliorated.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that HDL abrogates the induction of macrophages to an M1phenotype, as demonstrated by a reduction in the cell surface markers CD192 and CD64, as well as by decreased expression of MCP-1 (CCL2) [52]. HDL inhibits ERK1/2 and STAT3 phosphorylation in M1 macrophages [52]. HDL also increases expression of the M2 markers Arg1 and Fizz-1 via a mechanism requiring STAT6 [53].…”
Section: Resultsmentioning
confidence: 99%
“…63 HDL also inhibits the phenotype and function of M1 by decreasing the M1-specific markers and inflammatory genes TNF-α, IL-6, and MCP-1 via redistribution of membrane caveolin-1 and phosphorylation of ERK1/2 in human macrophages. 64 However, HDLmediated cholesterol efflux was impaired under the obese state in humans, 65 which was related to elevated monocytes, indicating a pro-inflammatory state in these subjects. 66 A recent study that reported the proteomic composition of HDL, but not the efflux capacity, reflects the differential mediation effects of reverse cholesterol transportation by saturated and monounsaturated fat diets in mice.…”
Section: Cholesterol Metabolismmentioning
confidence: 99%
“…Promoting intracellular cholesterol efflux by increasing HDL in macrophages has been found to induce the polarization of macrophages to the M2 phenotype, thus improving inflammation, oxidative damage, and AS in apoE knockout mice . HDL also inhibits the phenotype and function of M1 by decreasing the M1‐specific markers and inflammatory genes TNF‐α, IL‐6, and MCP‐1 via redistribution of membrane caveolin‐1 and phosphorylation of ERK1/2 in human macrophages . However, HDL‐mediated cholesterol efflux was impaired under the obese state in humans, which was related to elevated monocytes, indicating a pro‐inflammatory state in these subjects .…”
Section: Micro‐environmental and Intracellular Metabolism On Atm Polamentioning
confidence: 99%